CdO: SnO2 Composite UV-Assisted Room Temperature Ozone Sensor - Salman, Mohammed O.; Kadhim, Mohammed A.; Khalefa , Abed A. (Iraqi Journal of Science, 2023)
Cadmium-tin oxide (CSO) thin films were fabricated by spray pyrolysis method at different substrate temperatures (Ts). The results showed a significant effect of Ts on the surface morphology and the electrical properties, which in turn has a significant effect on sensor gas sensitivity. The sample prepared at 400 °C appeared in the form of a donut shape, which has the best ozone sensitivity. No ozone sensitivity appeared in-dark, while showed good sensitivity when illuminated with UV at room temperature (RT). The study showed that the photon exposure method can substitute for the conventional method of sensors heating.